Ionic Liquids for the Selective Solvent Extraction of Lithium from Aqueous Solutions: A Theoretical Selection Using Cosmo-Rs - Romero-Figueroa, J; Quijada-Maldonado, E; Araya-Lopez, C; Olea-Chandia, F; Villarroel-Utreras, E (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In this study, the theoretical design of ionic liquids (ILs) for predicting selective extraction of lithium from brines has been conducted using COSMO-RS. A theoretical model for the solvent extraction (SX) of the metal species present in brines was established considering extraction stoichi-ometry, the distribution of the extractants between aqueous and IL phases, and IL dissociation in the aqueous phase. Theoretical results were validated using experimental extraction percentages from previous works. Results indicate that, in general, the theoretical results for lithium extraction follow experimental trends, except from magnesium extraction. Finally, based on the model, an IL was proposed that was based on the phosphonium cation as the extractant, along with the phase modifier tributylphosphate (TBP) in an organic diluent in order to improve selectivity for lithium extraction over sodium. These results provide an insight for the application of ILs in lithium pro-cessing, avoiding the long purification times reported in the conventional process. © 2022 by the authors. Li-censee MDPI, Basel, Switzerland.